2014
DOI: 10.1039/c3cp54700k
|View full text |Cite
|
Sign up to set email alerts
|

Photo-active and dynamical properties of hematite (Fe2O3)–water interfaces: an experimental and theoretical study

Abstract: The dynamical properties of physically and chemically adsorbed water molecules at pristine hematite-(001) surfaces have been studied by means of equilibrium Born-Oppenheimer molecular dynamics (BOMD) in the NVT ensemble at 298 K. The dissociation of water molecules to form chemically adsorbed species was scrutinised, in addition to 'hopping' or swapping events of protons between water molecules. Particular foci have been dynamical properties of the adsorbed water molecules and OH -and H 3 O + ions, the hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 53 publications
(111 reference statements)
1
25
0
Order By: Relevance
“…It is noted that additional calculations (not shown here) demonstrate the same qualitative behaviour with similar features of hysteresis and multiplicity of solutions (i.e., bi-stable regimes) over a wide range of parameters spanning orders of magnitude of the respective rate constants, confirming the robustness of our model predictions. Moreover, the simple ER mechanism typically used to describe water photo-oxidation on haematite photoanodes 24 , 25 , 34 , 35 cannot yield such hysteresis because it lacks nonlinearity in the kinetic equations of its elementary steps (see Model equations and numerical computations in Methods for details).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that additional calculations (not shown here) demonstrate the same qualitative behaviour with similar features of hysteresis and multiplicity of solutions (i.e., bi-stable regimes) over a wide range of parameters spanning orders of magnitude of the respective rate constants, confirming the robustness of our model predictions. Moreover, the simple ER mechanism typically used to describe water photo-oxidation on haematite photoanodes 24 , 25 , 34 , 35 cannot yield such hysteresis because it lacks nonlinearity in the kinetic equations of its elementary steps (see Model equations and numerical computations in Methods for details).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The consequences of this competition are unfolded by a nonlinear kinetic model that not only reproduced the experimental observations but also gave rise to unexpected predictions that were subsequently verified by further experiments. Unlike the linear models of water photo-oxidation on haematite that consider a multi-step reaction on a single surface site 24 26 , 34 , 35 , as in Eley–Rideal (ER) reactions, our work suggests that splitting the reaction into two sites, as in LH reactions, enabled here by the presence of H 2 O 2 in the electrolyte, gives rise to nonlinear behaviour and facilitates the collection of photo-generated holes by oxidized surface species that help to level the potential of the elementary steps involved in the reaction 20 . The knowledge gained from this work may explain the behaviour observed for some common water oxidation co-catalysts based on cobalt 36 38 , and be also used to rationally design co-catalysts that facilitate water oxidation via a two-site process 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Their later work [15] showed that upon contact with water the surface can easily be covered with O atoms and/or OH groups. Low energy barriers for water dissociation on iron-rich hematite surface were confirmed by a combined ab initio molecular dynamics and experimental studies [16]. Calculation of the isolated water molecule on an Fe-and O-terminated (0001) surfaces yielded the adsorption energy of merely 0.49eV for the O-terminated surface [17].…”
Section: Introductionmentioning
confidence: 85%
“…The prepared sample mimics the XRD pattern of JCPDS no. 00‐001‐1053 which represents hematite . The FTIR spectrum shows characteristics peaks at 463 and 538 cm −1 and confirms the formation of Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 73%
“…00-001-1053 which represents hematite. [42] The FTIR spectrum shows characteristics peaks at 463 and 538 cm À 1 and confirms the formation of Fe 2 O 3 . Peaks between 1300-1700 cm À 1 correlate with CN bonding interactions.…”
Section: Resultsmentioning
confidence: 74%